2016
DOI: 10.1590/1807-1929/agriambi.v20n4p378-384
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort index, physiological variables and performance of quails fed with protein reduction

Abstract: A B S T R A C TThe objective of this study was to determine the effects of environment and electrolyte balance on environmental, physiological and productive indices of Japanese quails. For the experiment, 288 quails were distributed in a randomized block design with six treatments and six replicates of eight birds per experimental unit. The treatments consisted of one basal feed with 20.0% of crude protein (CP) and the others with a reduction of 3.0% CP to achieve six electrolyte balance levels (166.54; 153.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Egg quality can be affected by the levels of salt in the water or feed. However, salinity levels of up to 6.0 dSm -1 did not change the weight and percentage of albumen, which were similar to those reported by Lima et al (2015) and Rodrigues et al (2016). The latter papers did not find an effect of increasing sodium levels in the feed and electrolyte balance, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Egg quality can be affected by the levels of salt in the water or feed. However, salinity levels of up to 6.0 dSm -1 did not change the weight and percentage of albumen, which were similar to those reported by Lima et al (2015) and Rodrigues et al (2016). The latter papers did not find an effect of increasing sodium levels in the feed and electrolyte balance, respectively.…”
Section: Resultssupporting
confidence: 87%
“…The respiratory frequency of quails exposed to the heated environment was higher. This is a protection mechanism that increases evaporation in the exhaled air and releases internal heat in the evaporative form to maintain body thermal balance (Rodrigues et al, 2016;Silva et al, 2017), but it can lead to production losses. S. M. Santos et al (2014) reported this increase in the respiratory rate in quails kept at temperatures from 30 to 33ºC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight of a quail egg can vary between 10 and 13 g. Even under thermal stress, quails are able to maintain production and quality of the products (Guimarães et al, 2014;Rodrigues, Furtado, Costa, Nascimento, & Cardoso, 2016;Petrucci et al, 2017). However, these variables can be reduced in quails kept under thermal stress (El-Tarabany, 2016;Santos et al, 2017;Silva et al, 2017;Akdemir et al, 2019), due to the reduction in food intake, reduced digestibility of diet components, and mobilization and use of body reserves to maintain body temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the low applicability of the GTHI to assess the comfort of broiler chickens is emphasized, as well as the plumage, feather and skin characteristics of the broiler, the wind speed coming into the building and the intrinsic capacity of each species to eliminate endogenous heat are other variables that must be regarded for the elaboration of thermal comfort indexes for broilers. The rectal temperature and the surface temperature of the broilers are important physiological variables to verify whether the animal is in comfort (GUIMARÃES et al, 2014;RODRIGUES et al, 2016). No effect (P<0.05) of the roof paint was observed for the physiological variables.…”
Section: Resultsmentioning
confidence: 99%